(untitled) (Research, Society and Development, 2020)
Bread loaves are widely consumed and their distribution is directly related to their shelf life. Bread conservation and security, in most cases, depend on preservative addition to prevent mold growth. Sorbic acid and its salts are widely used in bakery products, because they cannot be added directly in the dough, as they inhibit bakers’ yeast, its microencapsulated form will be released after fermentation, without losses in bread volume and process time. Texture, moisture and water activity analysis were carried out to verify the influence of microencapsulated sorbic acid addition, in a matrix of canola oil (50:50) (A) and coated in palm oil (85:15) (B) on bread shelf life and to evaluate bread staling, associated with moisture loss and increased firmness. The presence of molds determines bread shelf life and the best results were obtained for the concentrations of 0.05% (flour-based) for both encapsulation methods and 0.10% of the microencapsulated sorbic acid in a canola oil matrix, presenting a shelf life of at least 14 days.